Teacher’s Perception of Video-Based Learning in ELT for ASD Students in Inclusive Classroom - Putri, Milia (Universitas Jambi, Magister Program of English Education Department, 2026)
The integration of video-based learning has become increasingly common in inclusive English Language Teaching (ELT) classrooms as educators seek effective strategies to support students with Autism Spectrum Disorder (ASD). This study explored an English teacher’s perceptions of the use of video-based learning for students with autism in an inclusive classroom. Employing a qualitative case study design, the research involved an English teacher at an inclusive senior high school in North Sumatra, Indonesia. Data were collected through semi-structured interviews, classroom observations, and teacher reflective journals and were analyzed using thematic analysis. The findings revealed that video-based learning played an important role in supporting students’ emotional regulation, sustaining attention, and encouraging participation during classroom activities. Students demonstrated greater enthusiasm and engagement when exposed to visual and auditory content. However, a significant engagement–comprehension gap was identified. Although students were highly attracted to animations, sounds, and visual elements, they often experienced difficulty understanding the intended language content and instructional objectives. The findings further indicated that the effectiveness of video-based learning was strongly influenced by the selection of authentic and relevant materials and collaboration between the classroom teacher and the shadow teacher. These forms of support helped students connect visual information with linguistic meaning and participate more actively in language-learning activities. The study concludes that video-based learning can serve as a valuable instructional resource for students with autism when combined with appropriate pedagogical support, teacher agency, and collaborative practices that address both engagement and language comprehension within inclusive ELT classrooms.